A Case Report: Tuberculosis Drug Induced Liver Injury - Octariany Octariany; Vivin Gusrizal (Lembaga Pengembangan Kinerja Dosen, 2024)
Tuberculosis is one of the world's health problems, especially in developing countries. Treatment regimen with multiple first-line anti-tuberculosis drugs (ATD) such as Isoniazid, Rifampicin, Pyrazinamide, Ethambutol, and Streptomycin remains the most effective for treatment of tuberculosis. Adverse drug reactions (ADRs) to antituberculosis drugs may range from mild gastrointestinal disturbances to serious hepatotoxicity, peripheral neuropathy, and cutaneous adverse effects. We report a 65 year old male patient with a complaint of yellowish discoloration of sclera, nausea and vomiting after three days of initiation of ATD therapy. The patient has been diagnosed with Tuberculosis relapse and has been taking ATD since June 2024. The patient noted epigastric pain. Laboratory examination found an increase in bilirubin level and electrolyte imbalance. The treatment is in the form of discontinuation of ATD, supportive therapy and followed by hepatoprotective supplements. ATD should be discontinued in patients with hepatotoxicity and fixed drug eruption until liver function and clinical symptoms improve. Initiation of ATD administration is carried out by administering one by one regimen. The patient is currently experiencing antituberculosis drug-induced hepatotoxicity, which is managed by providing supportive care and different AT regimens were prescribed.